Reliability and usefulness of a self-regulated 6-km submaximal ergometer training test set in elite rowers - Clark, J.; McKune, A.; Wood, P. (International Journal of Sports Science & Coaching, 2025)
Incorporating tests into regular training sessions permits sport-specific and convenient monitoring of athletes without disrupting team preparation or adding to testing burden. However, few studies have investigated the measurement properties of training test sets for monitoring athletes. This study assessed the reliability and usefulness of a self-regulated 6-km rowing ergometer training-based test (6SRT) as a submaximal monitoring tool in elite rowers. In a repeated measures design, 43 (13 female) rowers at a national training centre were asked to perform the 6SRT according to a `firm-to-hard`/`threshold` session category goal at 22 strokes·min-1 in three consecutive weeks. Mean ± standard deviation 6SRT time, power output (PO), exercise heart rate (HRex) and rating of perceived exertion (RPE) were 22:18.0 ± 1:21.6 min:s, 70 ± 4% 2-km time trial PO, 87 ± 3% maximal HR and 16 ± 1, respectively. There were no significant between-trial effects (p = 0.101, n2p = 0.05) and differences between paired trials were trivial (Cohen's d < 0.2) for all variables. Intraclass correlation coefficients (ICC3,1: 0.62-0.98) were moderate to excellent for all responses except RPE (0.33). Coefficient of variation (CV: 0.6-3.5%) and typical error (TE: 0.7-4.1%) were low for all variables except HR recovery (HRR). Time, PO and HRex responses, and PO:HRex and PO:RPE intensity ratios showed TE = smallest worthwhile change (SWC). The 6SRT shows acceptable reliability and usefulness under stable field conditions to be a valuable training test set for monitoring high-level rowers when maximal tests are undesirable or laboratory tests are inaccessible.